Reading motivation, self-regulated reading strategies and English vocabulary knowledge: Which most predicted students’ English reading comprehension? - Li, Hong; Gan, Zhengdong (Frontiers in Psychology, 2022)
This study explored how reading motivation, self-regulated reading strategies and English vocabulary knowledge influenced students’ English reading comprehension simultaneously in one model. A total of 543 students from five universities in Southern China completed a reading motivation questionnaire, a reading strategy questionnaire, two vocabulary knowledge tests, and a reading comprehension test. Multiple regression analysis results showed that reading efficacy and enjoyment, and vocabulary knowledge (i.e., both vocabulary breadth and depth) significantly predicted reading comprehension. When students were grouped into high, average, and low achievers on the reading test, monitoring strategies and vocabulary depth were found to significantly predict reading comprehension for the high achievers.